Nomogram to predict an endometrial thickness above 7.5 mm in the frozen embryo transfer cycle of women with a thin endometrium. Issue 2 (February 2022) - Guo, Zizhen; Chen, Wei; Wang, Yuqing; Chu, Ran; Xu, Xinxin; Zhang, Lixia; Yan, Lei; Ma, Jinlong
Abstract: Research question: Which characteristics of patients with a thin endometrium (endometrial thickness [EMT] ≤7.5 mm on human chorionic gonadotrophin [HCG] trigger day) suggest the possibility of an EMT >7.5 mm in the subsequent frozen cycle? Design: Data were collected from the university-affiliated Centre for Reproductive Medicine between January 2013 and September 2019. Multivariable logistic regression was used to generate the final prediction model and construct the nomogram. Model performances were quantified by discrimination and calibration. Results: The predictive variables that entered the final model were: hysteroscopic adhesiolysis history, polycystic ovary syndrome status, application of clomiphene in the ovarian stimulation process, the ovarian stimulation protocol and the endometrial preparation protocol. The receiver operating characteristic (ROC) curve for the final model and validation cohort was 0.760 (95% confidence interval [CI] 0.722–0.797) and 0.713 (95% CI 0.664–0.759), respectively. Discrimination performed well in both the modelling and validation cohorts. Conclusions: In women with a thin endometrium (EMT ≤7.5 mm on HCG trigger day), the absence of a hysteroscopic adhesiolysis history, the presence of polycystic ovary syndrome, the application of clomiphene in the ovarian stimulation process, the application of a gonadotrophin-releasing hormone agonist short protocol, mild stimulation protocol, natural cycle protocol, and natural cycle for endometrial preparation are prognostic for an increased possibility of an EMT >7.5 mm in the subsequent frozen cycle.